Vig István: Verancsics Faustus Dictionariuma a korabeli európai kontextusban (Dictionarium Fausta Vrančića u onodobnome europskome kontekstu): Budapest: Tinta Könyvkiadó, 2011. 192 p. - Lukács, István (Slavia Centralis, 2020)
The article presents the work of István Vig, who gives a very detailed overview of the research that dealt with Faust Vrančić and his five-language dictionary, and at the same time adds his findings.
Keywords: review; István Vig; Verancsics Faustus Dictionariuma a korabeli európai kontextusban; Faust Vrančić; five-language dictionary